Reproduction of Social Interaction Space for Papuan Mothers' Trading Places in the Making and Arrangement of Sidewalks in Manokwari City: Case study: around Borobudur Market, Jalan Jenderal Sudirman, Manokwari City, West Papua - Tika Ade Putri Pattikayhatu; Sri Pare Eni; Ramos P Pasaribu (MES Bogor, 2025)
The increase in urban activities that are not followed by good urban spatial planning has caused a decline in environmental quality, one of which is seen from the emergence of street vendors who dominate public spaces and carry out buying and selling activities along the roads and sidewalks. This picture can be found in several locations in Manokwari City, such as on Yos Sudarso Sanggeng street, Angkasa Mulyono street, and Jenderal Sudirman street, which are filled with Papuan mothers traders along the roadsides and sidewalks. The location of the garden which is far from home is also the reason they have to sell on the side of the road so that their goods are easily seen and sold quickly, so these Papuan mothers use the sidewalks and roadsides as spaces that are the main market orientation for selling their garden produce. The spaces formed by Papuan mothers when selling have the same patterns as in several research locations that will be studied. The purpose of this study is to identify the factors that encourage Papuan mothers to prefer selling on the roadside or sidewalk, and to find out ideas in organizing and arranging sidewalks for Papuan mothers who sell. This study uses a qualitative method that can produce descriptive data obtained from literature reviews, field observations, and interviews with various informants directly or indirectly through questionnaires and documentation. This study also uses a triadic approach that will discuss spatial practices, spatial representation and representational space to better understand the reproduction of social interaction space for Papuan mothers' selling places at the research location. The results of this study are expected to provide recommendations to the government in the form of an open market design concept on the sidewalk for Papuan mothers as the identity of the city of Manokwari.